SMEs an Economic Outlook: Array - Rexhepi, Aziz Nebih; Rexhepi, Besarta; Meha, Arbresha; Halili, Njazi (Acta Universitatis Danubius. Œconomica, 2020)
In the event of time outside the southeast and west of Kosovo, the SME was replaced by the drivers of economic development.Its economic development is the framework for political and economic macroeconomics, and the state secret lies in the development of SMEs. This is the first part of the truth, while the latter is simpler, SMEs' philosophy depends on entrepreneurs and management. in promoting and developing SMEs, new management salvage attempts, WoodThis includes the effective management of software, software, software, structures, people and resources as well as control stations with control. This process reviews the combination of common sense and power, the ability, the need risks and the specific knowledge in planning, organization, coordination, motivation and control as well as the organization and the mission. Nutz. the more effective and efficient.One of the main tasks of managers is to motivate and inspire people, and to create vision and create new challenges, where motivation is something that works in a person to bring himself to the best. Goaloriented, mother for the family and the company in which we work, goes well